Pre-sleep protein ingestion increases mitochondrial protein synthesis rates during overnight recovery from endurance exercise: a randomized controlled trial - Trommelen, J.; van Lieshout, G. A. A.; Pabla, P.; Nyakayiru, J.; Hendriks, F. K.; Senden, J. M.; Goessens, J. P. B.; van Kranenburg, J. M. X.; Gijsen, A. P.; Verdijk, L. B.; de Groot, L. C. P. G. M.; van Loon, L. J. C. (Sports Medicine, 2023)
Background: Casein protein ingestion prior to sleep has been shown to increase myofibrillar protein synthesis rates during overnight sleep. It remains to be assessed whether pre-sleep protein ingestion can also increase mitochondrial protein synthesis rates. Though it has been suggested that casein protein may be preferred as a pre-sleep protein source, no study has compared the impact of pre-sleep whey versus casein ingestion on overnight muscle protein synthesis rates. Objective: We aimed to assess the impact of casein and whey protein ingestion prior to sleep on mitochondrial and myofibrillar protein synthesis rates during overnight recovery from a bout of endurance-type exercise. Methods: Thirty-six healthy young men performed a single bout of endurance-type exercise in the evening (19:45 h). Thirty minutes prior to sleep (23:30 h), participants ingested 45 g of casein protein, 45 g of whey protein, or a non-caloric placebo. Continuous intravenous l-[ring-13C6]-phenylalanine infusions were applied, with blood and muscle tissue samples being collected to assess overnight mitochondrial and myofibrillar protein synthesis rates. Results: Pooled protein ingestion resulted in greater mitochondrial (0.087 ± 0.020 vs 0.067 ± 0.016%·h-1, p = 0.005) and myofibrillar (0.060 ± 0.014 vs 0.047 ± 0.011%·h-1, p = 0.012) protein synthesis rates when compared with placebo. Casein and whey protein ingestion did not differ in their capacity to stimulate mitochondrial (0.082 ± 0.019 vs 0.092 ± 0.020%·h-1, p = 0.690) and myofibrillar (0.056 ± 0.009 vs 0.064 ± 0.018%·h-1, p = 0.440) protein synthesis rates. Conclusions: Protein ingestion prior to sleep increases both mitochondrial and myofibrillar protein synthesis rates during overnight recovery from exercise. The overnight muscle protein synthetic response to whey and casein protein does not differ.